Fungsionalisasi Undang-Undang Darurat, Nomor 1 tahun 1951 sebagai Suplementasi dari Pasal 284 Kitab Undang-Undang Hukum Pidana Indonesia - Henni Muchtar; Muhammad Prima Ersya (Nagari Law Review, 2019)
The Penal Code of Indonesia as the heritage of Colonial Regime, in some instances is not in line with the people of Indonesia. One of them is that the article 284 concerning the prohibition of adultery, that has difference in concept with the values owned by Indonesian people. Therefore, there should be a breakthrough that the article adopts contemporary condition and be in line with the way of life of the people of Indonesia, especially related the first pillar of Pancasila, that is believe in one God. The purpose of this article is to discuss and convey the idea of the existence of Emergency Law No. 1 of 1951 concerning Temporary Measures in Organizing the Unity of the power and procedure of Civil Courts as supplementation of the article 284 of the Penal Code. This research applied normative juridical method and applicable law approach. The result of this study finds that Article 284 of the Penal Code could basically be accepted as one of the offense entities, but it is considered as lack Indonesia's spirit, even some consider that it not as a form of values in Indonesia people. The compliance between the law and the nation’s spirit is very important because the nation’s spirit is a source of material law that creates people’s legal awareness, as a guideline for law enforcement, as well as a source of the people’s law obidience. Considering the weaknesses and limitations of the article 284 of Penal Code in regulating adultery and the controversy of several articles in the draft Criminal Code which ended by the suspension of enactment and implementation, the Emergency Law No. 1 of 1951 can be enforced as supplementation of th article 284 of the Penal Code in order to maintain the balance and order in the society